Implementing the UN Sustainable Development Goals: How Is Health Framed in the Norwegian and Swedish Voluntary National Review Reports? - Ida Lillehagen; Kristin M. Heggen; Göran Tomson; Eivind Engebretsen (Kerman University of Medical Sciences, 2022)
BackgroundThe United Nations (UN) Sustainable Development Goals (SDGs) are parts of an ambitious framework for global development, the 2030 Agenda. Voluntary national reviews (VNRs) are described as "cornerstones" in the follow-up system, which is premised on international sharing of knowledge and experience. Norway and Sweden are among the world's most sustainable countries, aiming to be leaders in the implementation of the SDGs. The objective of this article is to investigate and compare how health is framed in the VNRs of these two high-income countries, and to discuss the implications of these framings for potential actions. MethodsDiscourse analysis inspired by the concept of 'framing,' which refers to the discursive presentation of an issue where certain problem definitions and solutions are privileged over others. Frames are structures that organise and direct attention to particular aspects of reality, and define what is seen. ResultsOur analysis demonstrates that in the Norwegian VNR (NVNR), the issue of health is simplistically framed, focusing on the favourable situation of the majority, thus providing weak grounds for transformative action. In the Swedish VNR (SVNR), health is framed to highlight health as inextricably tied to societal inequalities. This underscores the need for integrated political action and leadership to counteract structural differences with negative consequences for health. ConclusionAnalysis of the two VNRs studied found a difference in how health is framed in these documents and these frames point to differences in approach and capacity to address health inequities and realise the holistic and integrative concept of health promoted in the 2030 Agenda. To realize the Agenda's vision of "leaving no one behind" discourses of implementation that support the Agenda's inclusive and holistic ambition must be developed. Further development of the follow-up and review system should acknowledge and address how frames can limit or enable integrative actions and are therefore important drivers of change.